Providing a Model to Protect the Rights of Service Recipients in Hospitals - Mohammad Ali Fotuhi; Somayeh Hesam; Irvan Masoudi Asl; Mohsen Najafikhah (Health, Spirituality and Medical Ethics)
Background and Objectives: Service recipients in the hospital have rights due to unique physical and mental conditions. The increasing complexity of treatment systems, the increase in treatment costs, and the increase in awareness and expectations of service recipients have made it necessary to protect service recipients by the government and hospitals. This study was conducted to design a model to protect the rights of service recipients in Iranian hospitals. Methods: This research was conducted using a mixed-methods approach (quantitative and qualitative). The questions of the researcher-made questionnaire were finalized after interviews with experts and two rounds of soliciting expert opinions using the Delphi method. The finalized questionnaire was then administered to service recipients who were hospitalized. Data were extracted and analyzed using SPSS software, version 19 and SmartPLS software, version 3 using exploratory and confirmatory factor analysis. Results: Effective factors in protecting the rights of service recipients in Iranian hospitals were classified into ten main axes: strategic, information, patient-centered care, human resources, managerial, policy-making, physical resources, control, education, and insurance, along with 51 items. Among the results, the most crucial axis identified was strategy, with the sub-axis of legislation and drafting executive regulations to ensure the legal protection of the rights of service recipients. Conclusion: Protecting the rights of service recipients in Iranian hospitals requires the provision of necessary infrastructures and mechanisms from the macro level to the hospital level. This issue will increase patient satisfaction and fulfill the government’s obligations in this field.